Human Solid Tumors Contain High Endothelial Venules: Association with T- and B-Lymphocyte Infiltration and Favorable Prognosis in Breast Cancer - Ludovic Martinet; Ignacio Garrido; Thomas Filleron; Sophie Le Guellec; Elisabeth Bellard; Jean‐Jacques Fournié; Philippe Rochaix; Jean‐Philippe Girard (2011)
The mechanisms governing infiltration of lymphocytes into tumors remain poorly characterized, in spite of the critical impact of these cells on patient prognosis and therapeutic responses. High endothelial venules (HEV) are blood vessels found in lymphoid tissues, specialized in lymphocyte recruitment, but their implications in human cancer are unknown. In this article, we report the presence of MECA 79(+) blood vessels displaying all the phenotypic characteristics of HEVs in most of the 319 human primary solid tumors, including melanomas, breast, ovarian, colon, and lung carcinomas, analyzed. Tumor HEVs were specifically located within lymphocyte-rich areas, and their density within the tumor stroma was a strong predictor of infiltration by CD3(+) and CD8(+) T cells as well as B cells. Large-scale flow cytometric and quantitative reverse transcriptase-PCR analyses in freshly operated breast tumors revealed that high densities of tumor HEVs correlated with increased naive, central memory and activated effector memory T-cell infiltration and upregulation of genes related to T-helper 1 adaptive immunity and T-cell cytotoxicity. Finally, in a retrospective cohort of 146 invasive breast cancer patients, we found that high densities of tumor HEVs independently conferred a lower risk of relapse and significantly correlated with longer metastasis-free, disease-free, and overall survival rates. Together, our findings suggest that tumor HEVs function as major gateways for lymphocyte infiltration into human tumors, and may represent attractive targets for cancer diagnosis and therapy.